Mahasiswa tingkat kepaniteraan Universitas Hasanuddin Makassar, Indonesia - Irene Edith Rieuwpassa; Rahmat Rahmat; Karlina Karlina (DiscoverSys Inc., 2011)
The aim of this study was to determine the effectiveness of Aloe vera extract in inhibiting the growth ofStaphylococcus aureus and to measure the minimum inhibitory concentration (MIC) on the growth of the bacteria.The method using the manufacture of aloe extract, extract dilution, purified Staphylococcus aureus, MIC test andview the zone of inhibition. The results show that the (MIC) of Aloe extract was at concentration of 0.25. After astatistical test with ANOVA test on survey data (Î±<0.05), then the result obtained 0.000. This shows significantdifferences between various concentrations of Aloe vera extract in inhibiting the growth of Staphylococcus aureusbacteria. The higher the concentrationof Aloe vera extract, the more expand diameter of inhibition zone. Thusextracts of Aloe vera may be used to inhibit the growth of Staphylococcus aureus.